International dosage differences in fluoxetine clinical trials. - Patten, S; Cipriani, A; Brambilla, P; Nosè, M; Barbui, C (2005)
OBJECTIVE: International differences are thought to exist in dosages used by clinicians treating mood disorders. This study examined international dosage differences in antidepressant clinical trials, using a database formed and maintained as a component of a Cochrane review of comparative clinical trials of fluoxetine. METHODS: This systematic review included 132 studies. A detailed set of methodological features and results were abstracted from the original publications and entered into an electronic database. Mean and maximum fluoxetine dosages were compared across countries. To evaluate the dosages of comparison medications, a defined daily dosage (DDD) ratio was calculated as the trial mean dosage divided by the DDD for that drug. RESULTS: Both the maximum and mean dosages for fluoxetine and comparison medications were higher in trials conducted in the US (fluoxetine weighted mean dosage 49.18 mg; 95% CI, 41.30 to 57.05), compared with trials conducted in Europe (fluoxetine weighted mean dosage 29.98 mg; 95% CI, 25.28 to 34.68). Since most clinical trials were conducted in Europe or the US, we could not determine whether different dosages tended to be used in other regions. CONCLUSIONS: International differences in prescriber behaviour may influence, and in turn be influenced by, the conduct of clinical trials. It is difficult to reconcile such differences with the principles of evidence-based medicine.